Legal Review of Utilization Cooperation Forest For Tour Nature in the Work Area Perum Perhutani Divisi Regional Jawa Tengah - Nurul Agustin Damayanti (Law Research Review Quarterly, 2026)
Study this study in a way critical construction authority and practice cooperation utilization forest in the form of utilization service environment for tourism​ nature implemented by Perum​ Perhutani Central Java Regional Division in perspective law state administration and law forestry. Focus main in study this lies in legitimacy authority, form delegates used, as well relation between instrument administrative and agreements cooperation in practice management state forests. Research this use method juridical normative with approach conceptual and legislative, which is strengthened with empirical data through interviews and reviews document. Analysis done in a way qualitative for identify suitability between norms and implementation. Research results show that authority Perum Perhutani in utilization forest in the form of utilization service environment for tour natural in a way normative based on mandate constitutional state control over source power nature and rules legislation in the field of forestry. Authority the executed through mechanism delegation administratively limited by value parameters, term time and procedures internal approval. In in practice, cooperation tour natural form construction law hybrid between law public and law private. Although has been formally fulfil principle legality, there is potential shift function area if supervision no done in a way strict and consistent. Therefore that, strengthening accountability, transparency, and integration principle sustainability become prerequisite important for ensure that utilization tour still is at in corridor law and not reduce function ecological state forests.